Infectious Diseases Clinician's Variation in the Management of Pediatric Staphylococcus aureus Bacteraemia and Equipoise for Clinical Trials - Campbell, Anita J.; Tong, Steven Y. C.; Davis, Joshua S.; Munro, Alasdair P. S.; Blyth, Christopher C.; Bowen, Asha C. (Frontiers in Pediatrics, 2019)
Abstract Background Paediatric Staphylococcus aureus bacteraemia is now the leading cause of community- acquired blood-stream infection; however, our understanding of management practices by treating clinicians is limited. Methods The authors designed a web-based clinician survey with support from the Australian and New Zealand Paediatric Infectious Diseases group, of the Australasian Society of Infectious Diseases. Clinicians were presented with three paediatric cases of varying severity. Antibiotic choice, durations of intravenous and oral therapy and research priorities for paediatric SAB trials were gauged. Results and conclusion Large variation in antibiotic prescribing amongst clinicians for paediatric S. aureus bacteraemia is demonstrated and increased, corresponding with escalating case complexity and persisting MRSA bacteraemia. Most clinicians chose defining optimal duration of therapy for S. aureus bacteraemia as their top clinical trial priority. These findings highlight the importance of prioritising paediatric S. aureus bacteraemia clinical trials, to inform guidelines and best practice management.